2022
DOI: 10.1039/d2cc02354g
|View full text |Cite
|
Sign up to set email alerts
|

High-conductivity thiocyanate ionic liquid interface engineering for efficient and stable perovskite solar cells

Abstract: A high-conductivity thiocyanate ionic liquid (EMIMSCN) was introduced into perovskite solar cells for the first time. The high conductivity of EMIMSCN ensures adequate supply of free SCN- anions and EMIM+...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…49 These results illustrate that TA-MN indeed owns better passivating ability and thus achieves suppressed trap-assisted recombination more effectively, which can indirectly verify the synergistic passivating effect of the TA-MN molecule. 18,50 The dependency of V OC and J SC on the light intensity was investigated to gain deeper insight into the carrier recombination mechanisms of PSCs. 51 According to J SC = I a , the J SC alters as a function of the light intensity in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…49 These results illustrate that TA-MN indeed owns better passivating ability and thus achieves suppressed trap-assisted recombination more effectively, which can indirectly verify the synergistic passivating effect of the TA-MN molecule. 18,50 The dependency of V OC and J SC on the light intensity was investigated to gain deeper insight into the carrier recombination mechanisms of PSCs. 51 According to J SC = I a , the J SC alters as a function of the light intensity in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, hydrophilic components such as ionic groups should also be included in these molecules to Fig. 21 Chemical structures of PF5A, PF5N, PF5O, 145 QPSCl, 146 PL-A, 147 FSA, 148 LPEI, 149 BED, 150 DMIMB, 151 C4I, C6I, 152 EMIMSCN, 154 BZMIMCl, 155 EMIM-TFSI, 157 and MOCs. ensure adequate coverage of the perovskite films.…”
Section: Improvement Of Atmospheric Stabilitymentioning
confidence: 99%
“…Finally, the PCE of [PEVIM]Cl‐modified PSCs increased from 12.49% to 14.19%, and maintained 91% of initial PCE at 85 °C in a nitrogen atmosphere for 360 h. Wang et al used IL 1‐ethyl‐3‐methylimidazolium thiocyanate (EMIMSCN) to modify the top surface of (FA 0.92 MA 0.08 )PbI 3 perovskite film. [ 66 ] The DFT calculation results showed that both EMIM + and SCN − could passivate the V I and Pb–I antisite defects of perovskite surfaces. Therefore, the EMIMSCN‐treated devices reached an efficiency of 22.55%.…”
Section: Ionic Liquids For Interface Modificationmentioning
confidence: 99%